2015
DOI: 10.1111/jpi.12210
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin uptake through glucose transporters: a new target for melatonin inhibition of cancer

Abstract: Melatonin is present in a multitude of taxa and it has a broad range of biological functions, from synchronizing circadian rhythms to detoxifying free radicals. Some functions of melatonin are mediated by its membrane receptors but others are receptor-independent. For the latter, melatonin must enter into the cell. Melatonin is a derivative of the amino acid tryptophan and reportedly easily crosses biological membranes due to its amphipathic nature. However, the mechanism by which melatonin enters into cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 61 publications
3
132
0
Order By: Relevance
“…It is a membrane protein that belongs to the transient receptors, which is a non-selective cation channel permeable to Ca 2þ . In this sense, the Ca 2þ influx triggered after TRPV4 stimulation is probably able to induce the release of melatonin as it occurs in other cells such as pinealocytes or retinal cells, although recently it has been demonstrated that melatonin could be transported by means of glucose transporters (Hevia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is a membrane protein that belongs to the transient receptors, which is a non-selective cation channel permeable to Ca 2þ . In this sense, the Ca 2þ influx triggered after TRPV4 stimulation is probably able to induce the release of melatonin as it occurs in other cells such as pinealocytes or retinal cells, although recently it has been demonstrated that melatonin could be transported by means of glucose transporters (Hevia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This type of glucose metabolism is termed aerobic glycolysis [83], a phenomenon inhibited by melatonin, thus reducing glucose metabolism. Melatonin decreases the uptake of glucose and modifies the expression of the GLUT1 transporter in prostate cancer cells, supporting a critical role in the uptake of glucose by cancer cells [84].…”
Section: Inhibition Of Aerobic Glycolysismentioning
confidence: 99%
“…This entry was thought to be related to simple diffusion of melatonin, which is highly lipophilic, through the plasma and mitochondrial membranes. While this possibility is still viable, melatonin has been shown to enter cells via the GLUT1 transporter [178] and by means of the PEPT1/2 oligopeptide transporters [180]. The latter proteins also exist in mitochondrial membranes where they presumably aid in the rapid uptake of melatonin against a gradient.…”
Section: Discussionmentioning
confidence: 99%
“…While this remains a possible route for its entrance into cells, recent studies have examined active transport means by which it passes through membranes. The first serious attempt to determine how high intracellular levels of melatonin are achieved, Hevia et al [178] examined the uptake of melatonin in a variety of normal and cancer cells. For this purpose, cells were incubated in a solution containing pharmacological concentrations (1 mM) of melatonin.…”
Section: Intrinsic Sources Of Melatoninmentioning
confidence: 99%